IMPACT OF DOMESTIC COOKING (BOILING) ON PHENOLIC CONTENTS AND ANTIOXIDANT ACTIVITY IN VARIOUS LENTIL CULTIVARS - Mokrani, Abderrahmane (Food and Feed Research, 2026)
Lentils (Lens culinaris Medik) are among the most widely consumed foods in the world; however, they are mainly cooked by boiling, which causes the loss of antioxidant compounds. This study aimed to evaluate the effects of boiling on the phenolic content—specifically total phenolic content (TPC), total flavonoid content (TFC), and total proanthocyanidin content (TPAC)—as well as antioxidant activity, including total antioxidant activity (TAA), DPPH radical scavenging activity (DPPH-RSA), and ferric reducing power (FRP) in various lentil cultivars. Six commercially available lentil samples (black, brown, green, dehulled red, white, and dehulled yellow) were analyzed. TPC, TFC, and TPAC were measured using Folin-Ciocalteu, AlCl₃·6H₂O, and butanol–HCl spectrophotometric methods, respectively, alongside antioxidant activity assessments (TAA, DPPH assay, and FRP) before and after cooking. The results revealed that whole lentils contained higher levels of TPC, TFC, and TPAC, as well as greater antioxidant activities (TAA, DPPH-RSA, and FRP) compared to dehulled lentils. Furthermore, whole lentils with dark seed coats (green and black) exhibited superior values for TPC, TFC, TPAC, TAA, DPPH-RSA, and FRP compared to varieties with lighter-colored skins (brown and white). These findings indicate that the presence and color of the seed coat significantly influence the phenolic content of lentil seeds. Boiling lentils for 30 minutes resulted in a substantial decrease in TPC, TFC, TPAC, and antioxidant activity (TAA, DPPH-RSA, and FRP). In addition to their nutritional benefits, lentils can serve as excellent sources of antioxidants and may be utilized as functional ingredients in the production of nutraceuticals and health foods within the food industry
Keywords: lentil; phenolic compounds; antioxidant activity; cultivar; raw; cooking (boiling)